Assessment of Aflatoxin M1 Levels by Enzyme-linked Immunosorbent Assay in Yoghurt Consumed in Tehran, Iran - Reza Tavakoli, Hamid; Kamkar, Abolfazl; Riazipour, Majid; Sasan Mozaffari Nejad, Amir; Rafati Shaldehi, Hassan (Asian Journal of Chemistry, 2012)
Due to their nutritional value, milk products are popular in Iran. However, aflatoxin M1 (AFM1) in milk and dairy products is considered to pose certain hygienic risks for human health. This study was undertaken to determine the occurrence of aflatoxin M1 in 50 yoghurt samples from 2 dairy factories in summer 2008 and winter 2009. Enzyme-linked immunosorbent assay (ELISA) technique was used for the analysis of yoghurt samples. Aflatoxin M1 was found 70 % in the yoghurt samples, ranging from 21.1 to 137.6 ng/kg. Toxin level is 17.14 % of the samples exceeded the Iranian national standard limit i.e. 50 ng/kg. Also, statistically significant seasonal effect was found for yoghurt samples. The result showed that the contamination of the yoghurt in such a level could be a serious public health problem.